2021
DOI: 10.1109/jphot.2021.3119960
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Enhancement for Fiber Bragg Grating Strain Sensing Based on Optoelectronic Oscillator With Vernier Effect

Abstract: Based on a dual-loop optoelectronic oscillator (OEO) with Vernier effect, a scheme of fiber Bragg grating (FBG) interrogation system with an improved scale factor has been proposed and experimentally demonstrated. Functioning as the optical carrier of the OEO, the reflection signal of two cascaded FBGs is divided into two optical beams by using a wavelength division multiplexer (WDM). The two optical beams at different wavelengths travel along single mode fibers with different lengths. After combined together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…X. Z. Tian et al reported a dual-loop OEO based on Vernier effect to improve the measurement sensitivity of strain [8] . To resolve the problem of cross sensitivity, dual-frequency OEO was proposed [9,10] , which can generate two oscillating signals with different sensitivities in response to strain and temperature, thus temperature compensation can be realized.…”
Section: Introductionmentioning
confidence: 99%
“…X. Z. Tian et al reported a dual-loop OEO based on Vernier effect to improve the measurement sensitivity of strain [8] . To resolve the problem of cross sensitivity, dual-frequency OEO was proposed [9,10] , which can generate two oscillating signals with different sensitivities in response to strain and temperature, thus temperature compensation can be realized.…”
Section: Introductionmentioning
confidence: 99%
“…The multiplexing capacity of the FBG sensor is limited by the bandwidth of the laser source and FBG. For a light source with a 40 nm bandwidth, for the sake of safety, each optical channel can only access up to 20 FBGs in engineering applications [ 27 ]. As a result, it cannot be used for large-scale train-track status detection.…”
Section: Introductionmentioning
confidence: 99%